2014
DOI: 10.7554/elife.03908
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiological dynamics of Ebola outbreaks

Abstract: Ebola is a deadly virus that causes frequent disease outbreaks in the human population. In this study, we analyse its rate of new introductions, case fatality ratio, and potential to spread from person to person. The analysis is performed for all completed outbreaks and for a scenario where these are augmented by a more severe outbreak of several thousand cases. The results show a fast rate of new outbreaks, a high case fatality ratio, and an effective reproductive ratio of just less than 1.DOI: http://dx.doi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 11 publications
1
31
1
1
Order By: Relevance
“…Recent studies using those methods found the Sierra Leone outbreak had an R 0 of between 2.02 (95% CI; 1.79-2.26) 14 and 2.53 (2.41-2.67) 15 and the lower bound of previous outbreaks ranged between 1.34 and 3.65. 16 However, sequences collected from patients receiving care will account for public health control measures and so these methods should therefore be considered as measuring the R e . Indeed, our estimate is closer to the R e found using conventional count-based methods (ranging between 1.38 and 1.5 for the 2014 Ebola outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies using those methods found the Sierra Leone outbreak had an R 0 of between 2.02 (95% CI; 1.79-2.26) 14 and 2.53 (2.41-2.67) 15 and the lower bound of previous outbreaks ranged between 1.34 and 3.65. 16 However, sequences collected from patients receiving care will account for public health control measures and so these methods should therefore be considered as measuring the R e . Indeed, our estimate is closer to the R e found using conventional count-based methods (ranging between 1.38 and 1.5 for the 2014 Ebola outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…The growing concern over the repeated emergence of EVD (7,8) has stimulated many studies on these outbreaks, in particular on the most recent one in West Africa, trying to understand the transmission mechanisms and the effectiveness of containment strategies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). These studies, however, either used limited data at an early stage of the epidemic or assessed a single influential factor.…”
mentioning
confidence: 99%
“…Historically, outbreaks have been confined to isolated areas within Central Africa; however, the 2014 outbreak reached an unprecedented level, making this the largest outbreak since the discovery of the virus in 1976 (2).…”
mentioning
confidence: 99%